A study of a single phase grid connected pv inverter performance under a weak grid conditions and distorted grid voltage for Cambodia - Sovanna Phoeurn; Sakda Somkun (Institute of Advanced Engineering and Science, 2021)
A single-phase grid-connected PV inverter performance under a weak grid is a model designed to penetrate PV energy with a weak grid. Usually, this model gets complex and unstable in power system control such as THD growth, harmonic effects, voltage surges, inverter performance. Experimental results would present the impacts on the system which would lead to instability in the grid system. This study was based on inverter performance control, a weak grid control, the grid distortion examination, and harmonic effects. To optimize this grid system, hence, the proposed methods of oscilloscope and power meter were proportionally used to control the grid impacts and stabilities. The results showed that current THD in distorted grid voltage system surged to 8.88%. VPCC growth was 238.11V, equivalent to 8.23% in a weak grid (XL and R). Such a huge increase could prevent the grid system from transferring power for later operation. During the experiment, the inverter, S power and Q power performances stood for good operating processes without impacts on the grid performance. This method should be applied with a weak grid system because it provided information about grid stability control.